Coaches of elite athletes with disability: senior sports administrators` reported factors affecting coaches` recruitment and retention - Wareham, Y.; Burkett, B.; Innes, P.; Lovell, G. P. (Qualitative Research in Sport, Exercise and Health, 2019)
Sport for elite athletes with disability is gaining recognition comparable to its non-disabled counterpart, with Paralympians considered among the world`s elite athletes. The value of sports coaching to the development, training and success of athletes with disability is similarly recognised. This research explored the views and experiences of administrators and policymakers working at a senior level in Australian organisations with oversight of coaches of elite athletes with physical disability, focussing on factors influencing their recruitment and retention. Semi-structured interviews were held with 10 participants working in organisations with responsibility for a range of sports including athletics, swimming, wheelchair basketball, wheelchair rugby, equestrian sport, triathlon, cycling, rowing, goal ball, boccia, football and power lifting. Results identified that there were barriers to recruiting coaches to work with athletes with disability, primarily due to preconceptions of stigma, and the perceived need for disability-specific knowledge. However, the coaches` retention rates were substantially higher than that of coaches in general, with reported factors including personal satisfaction, richer interpersonal relationships and enhanced career progression.